As emoções das atividades físicas de aventura na natureza e a ressignificação do papel feminino - Silva, Renata Laudares [UNESP] (2004)
The aim of this qualitative study was to verify the relationship between the increase of female participation in nature adventure physical activities (N.A.P.A.) and the reshaping of the female role in society. The study was conducted in two parts. The first was a revision of literature regarding the theories in question. The second was exploratory research, using a structured interview as the instrument for data collection. The target research sample was composed of thirty women that frequently practise NAPA. A Content Analysis Technique was used to interpret the results. Four indicators were established: the motives of the female population being drawn to practise NAPA; the practical relationship between these activities and the female role; the difficulties and barriers encountered by females who practise NAPA; the effect of the practice of NAPA on the female role in society. According to the results, the motives for practising NAPA were mainly to be in contact with nature, to manage day-to-day tension and stress, and to gain new experiences among others. Most test subjects affirmed the relationship between the practice of NAPA and the female social role. This was justified by an increase of physical force, of courage, of determination, of endurance, and of the disposition to overcome challenges and obstacles, to use competence and persistance in difficult moments of diverse situations, to 160 review preservationist values, and finally, to rupture the age-old myth that brands the female public as the 'weaker sex'. Most test subjects denied the existence of any difficulties or barriers regarding the practice of NAPA. They told of support from the general male public, from friends and from relatives. Other elements such as physical force and physical conditioning facilitate the further practice of NAPA, according to some of the test subjects. Therefore, these factors cannot be considered to be the limiting factors of the practice. There appears to be other relevant aspects, particualrly psychological, such as emotion control and the ability to take quick action. These become important elements in the experimentation of these practices in nature. The test subjects spoke of the psychological, social, professional, and personal benefits with regards to the effect of NAPA on day-to-day life and their possible changes to female roles in society. From these results, we can conclude that NAPA effectively contribute to improved engagement in social, professional, and personal society. Faced with the most diverse situations, activity in nature affirm the attitudes and values of women and make them more confident in their actions. These women regard practising NAPA as a personal achievement. This goes a lot further than the small thoughts of simply occupying space or attempting to equal their male counterparts. These women strive for freedom, personal satisfaction and pleasure. In a natural environment, these women can meet their needs and desires. The study determined that the new signification of NAPA is a two-sided coin. Social changes interfere with the level of practice of NAPA, while these practices alter the most diverse aspects of society